2023
DOI: 10.1186/s12889-023-17143-z
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between family function and the incidence of overweight/obesity in children and adolescents in Chengdu city, Sichuan province of China: based on latent profile analysis

Xixi Jiang,
Xiufang Zhao,
Junxia Zhou
et al.

Abstract: Background Overweight/obesity in children and adolescents has become a global health problem, and family function may be associated with its occurrence. Studies exploring the association between family function and overweight/obesity in children and adolescents were performed in Western and Taiwan, China. To date, related studies haven’t been conducted in Mainland China. Objectives To investigate the current status of overweight, obesity, and famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…The current study reported that two-thirds of the families were functional compared to about one-third was dysfunctional. The current study was supported by the Chinese study conducted by Jiang et al (2023) and Pan et al (2021), which reported that about two-thirds of the families were normal.…”
Section: Discussionsupporting
confidence: 66%
“…The current study reported that two-thirds of the families were functional compared to about one-third was dysfunctional. The current study was supported by the Chinese study conducted by Jiang et al (2023) and Pan et al (2021), which reported that about two-thirds of the families were normal.…”
Section: Discussionsupporting
confidence: 66%